2014
DOI: 10.1016/j.biocon.2014.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Aliens in Antarctica: Assessing transfer of plant propagules by human visitors to reduce invasion risk

Abstract: International audienceDespite considerable research on biological invasions, key areas remain poorly explored, especially ways to reduce unintentional propagule transfer. The Antarctic represents a microcosm of the situation, with the numbers of established non-native species growing. Information to help reduce potential impacts is therefore critical. We measured the propagule load of seeds, and fragments of bryophytes and lichens (the number of other plant or animal fragments was too low to draw any conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 53 publications
(61 reference statements)
0
61
0
Order By: Relevance
“…The majority of records of aliens were from currently or formerly inhabited settlements suggesting their introduction was associated with higher levels of human traffic (Chown et al 2012;Huiskes et al 2014;Ware et al 2012); animal husbandry and commerce practices in settlements (Coulson et al 2013(Coulson et al , 2015; and/or generally more favourable local climates. Data permitting the formal testing of the relative roles of these plausible introduction mechanisms are not available.…”
Section: Alien Species In Svalbardmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of records of aliens were from currently or formerly inhabited settlements suggesting their introduction was associated with higher levels of human traffic (Chown et al 2012;Huiskes et al 2014;Ware et al 2012); animal husbandry and commerce practices in settlements (Coulson et al 2013(Coulson et al , 2015; and/or generally more favourable local climates. Data permitting the formal testing of the relative roles of these plausible introduction mechanisms are not available.…”
Section: Alien Species In Svalbardmentioning
confidence: 99%
“…), but adopting measures to ensure these activities do not present species invasion risks in the future seems prudent. Adopting a biosecurity framework modelled on existing Antarctic measures would provide more comprehensive protection (Hughes and Convey 2010;Huiskes et al 2014). Such a framework may prove difficult to implement at the panArctic scale, but regional frameworks should be achievable in light of the success experienced in the Antarctic.…”
Section: Implications For Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased activity of tourist operators in some places of the maritime Antarctic is also another matter of concern. Disturbance by trampling of the fragile moss and lichen communities has been monitored (Pertierra et al 2013), and protocols to avoid contamination and transfer of plant propagules by humans have been developed (Huiskes et al 2014).…”
Section: Terrestrial Biocomplexity: Function and Linkages In Land Andmentioning
confidence: 99%
“…However, no terrestrial species introduced to the Antarctic continent intentionally (mainly for scientific research reasons) have been formally identified as invasive (Smith 1996), but intentional introductions to most subAntarctic islands, before the adoption of legislation prohibiting or controlling this activity, have resulted in substantial impacts (see Convey and Lebouvier 2009). Under current legislative systems, unintentional introductions present the greatest threats to sub-Antarctic and Antarctic ecosystems (Frenot et al 2005), with non-native species potentially being introduced associated with visitors' clothing and personal effects Chown et al 2012b;Huiskes et al 2014), cargo Tsujimoto and Imura 2012), building material (Lee and Chown 2009) and fresh foods .…”
Section: Introductionmentioning
confidence: 99%